Pemberdayaan Literasi Rumah Baca Di Desa Kore Kecamatan Sanggar Kabupaten Bima - Alwi Alwi; Mawar Hidayanti; M. Rimawan; Ismunandar Ismunandar (CV. Devi Tara Innovations, 2025)
The Literacy House is a facility designed to encourage community participation, especially children and teenagers, to be more active in literacy activities, both in reading, writing and discussions. This community service program aims to reactivate and develop the Literacy House in Kore Village, Sanggar District, Bima Regency, in order to increase the reading interest and writing skills of the local community. By providing access to a variety of books and learning facilities, it is hoped that this Literacy House can become a place that supports the growth of non-formal education in the reading house community in KORE Village, Sanggar District, Bima Regency. The results of this service show very high enthusiasm from Youth and Community Shop leaders and it is hoped that this service will increase interest in reading, writing skills, as well as active participation in digital literacy activities for the people of KORE Village, Kec. Sanggar Bima Regency.